PERBEDAAN TEKNIK RELAKSASI NAFAS DALAM DAN TERAPI MUSIK TERHADAP KECEMASAN PASIEN OPERASI SECTIO CAESAREA DENGAN SPINAL ANESTESI - Rida Amini; Jenita Doli Tine Donsu; Agus Sarwo Prayogi (Caring : Jurnal Keperawatan, 2018)
Surgery or surgery is a stressor for patients because it can bring potential and actual threats to the body, integrity, and soul of a person, causing emotional reactions such as fear, anger, anxiety, and anxiety with symptoms such as frequent asking questions, anxiety, rapid pulse, increased tension 20 % to 30%. The cause of anxiety in patients with preoperative section Caesarea is more specific, namely the concern for self and the baby to be born. Preoperative patient anxiety is very important, one of the nursing actions to overcome anxiety problems in patients can be independent actions by nurses such as relaxation and distraction techniques. This study aims to determine the difference between giving deep breathing relaxation techniques and music therapy to the anxiety of patients with cesarean section surgery with spinal anesthesia. This research method is quasi-experimental with pre-test and post-test design. Sampling by purposive sampling with the treatment of deep breathing relaxation techniques as many as 37 respondents and 37 respondents with music therapy controls, according to the inclusion and exclusion criteria. Breath relaxation in effectively reducing the anxiety of patients with section cesarean surgery with significance (p = 0,000). Music therapy is also effective in reducing the anxiety of patients with section cesarean surgery with significance (p = 0,000). But there was no difference in the decrease in anxiety after administration of deep breathing relaxation techniques and music therapy with significance (p) 0.317. Conclusion Deep breathing and music therapy together can reduce the anxiety of patients undergoing section cesarean surgery. Both actions can be used to complement nursing interventions that are already in the hospital.